Public Perceptions of Deep-Sea Environment: Evidence From Scotland and Norway - Ankamah-Yeboah, Isaac; Xuan, Bui Bich; Hynes, Stephen; Armstrong, Claire W. (Frontiers in Marine Science, 2020)
Knowledge of people’s understanding of environmental problems is vital for the effective implementation of the ecosystem approach to marine management. This is especially relevant when conservation goals are aimed at ecosystems in the deep-sea that are remote to the consciousness of most people. This study explores public perceptions of the deep-sea environment among the Scottish and Norwegian public. It further analyses the relationships between respondents’ pro-environmental concerns towards the marine environment and personal characteristics using a multiple indicators multiple causes model. The results show that public knowledge of the deep-sea environment is low for Scottish and moderate for Norwegians. Awareness of cold-water corals was high for the Lofoten case study area amongst the Norwegian public and low for the Mingulay reef complex in the Scottish case. These differences might arise because Norway is known to host the world’s largest cold-water corals in the Lofoten area; a fact that has been well publicised. We find that most people think changes in the deep-sea have at least some effect on them. On average, the public perceive the deep-sea condition to be at most ‘fairly good’ but are dissatisfied with the management of it with approximately only one third or less thinking it is well-managed. Generally, the public perception from both countries show ecocentric attitudes towards the marine environment implying that they recognize the value of ecosystem services, the current ecological crisis and the need for sustainable management.